Association Between Paternal Separation During Early Childhood and Pubertal Timing Among Girls Using Longitudinal Birth Cohort in Japan - Katagiri, Aomi; Nawa, Nobutoshi; Fujiwara, Takeo (Frontiers in Endocrinology, 2021)
Introduction: Previous studies have shown that paternal absence leads to earlier pubertal timing among girls in high-income countries. Despite the low divorce rate in Japan, paternal separation is commonly seen due to a unique corporation system, tanshin funin, where employees relocate with their spouses and children. We examined paternal separation, including paternal absence (due to divorce or paternal death) and paternal tanshin funin, during early childhood as a predictor of earlier girl’s pubertal development, assessed as age at peak height velocity (PHV). Methods: This study examined 15 214 girls from a longitudinal survey conducted in Japan from 2001 to 2016 by the Ministry of Health, Labor and Welfare. Paternal separation was determined by the occurrence through annual surveys conducted at ages 0.5 to 4.5 years. Outcome was defined as age at PHV between ages 6 to 15 years. We conducted linear regression, adjusted for potential confounders and other covariates. Results: Continuous father cohabitation was seen in 88.7% of households, while paternal separation was experienced 1-2, 3-4 and 5 times (always) among 7.4%, 2.8% and 1.1% of households, respectively. Girls who confronted continuous paternal separation (5 times) experienced 0.42 years earlier (95% confidence interval (CI): -0.75, -0.10) age at PHV compared to their peers who always lived with their fathers. Conclusion: Girls who experienced paternal separation throughout ages 0.5 to 4.5 years experienced PHV earlier.